DOI: 10.18174/553410
|View full text |Cite
|
Sign up to set email alerts
|

Conserving Inequality : Subjugating black labour and hoarding property in South Africa’s private nature reserves

Abstract: Chapter 4 Conserving Inequality: how private conservation and property Chapter 4 Conserving Inequality: how private conservation and property developers 'fix' spatial injustice in South Africa developers 'fix' spatial injustice in South Africa 4.1 Introduction 4.2 Socioecological conservation fixes and spatial (in)justice 4.3 Historicizing spatial injustice in Hoedspruit 4.4 'Fixing' biodiversity (loss) to 'fix' spatial injustices 4.5 Mooring conservation in place 4.6 Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 146 publications
(258 reference statements)
0
1
0
Order By: Relevance
“…However, many conservation areas in South Africa are managed along the lines of a protectionist approach, with not only inadequate access and benefit-sharing for local communities [6,11,85], but also unilateral decision making. By excluding a large part of the population from the wildlife economy, conservation efforts actively reproduce social and spatial inequality [12]. Given the history of political struggle, diverging socio-economic circumstances and access to reserves [13], it is vital to develop solutions that acknowledge and address the disparities in influence, access, and values among stakeholders while seeking commonalities to reconcile their aspirations [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many conservation areas in South Africa are managed along the lines of a protectionist approach, with not only inadequate access and benefit-sharing for local communities [6,11,85], but also unilateral decision making. By excluding a large part of the population from the wildlife economy, conservation efforts actively reproduce social and spatial inequality [12]. Given the history of political struggle, diverging socio-economic circumstances and access to reserves [13], it is vital to develop solutions that acknowledge and address the disparities in influence, access, and values among stakeholders while seeking commonalities to reconcile their aspirations [19].…”
Section: Discussionmentioning
confidence: 99%
“…In its most transformative form, this requires land reform, citizen or co-management, addressing power imbalances between private landowners and local people, and recognising moral values and non-material injustices [94,95]. Similarly, job creation as a conservation benefit can range from temporary construction, cleaning, or fence maintenance jobs with poor labour conditions, to permanent jobs which offer training and opportunities for career growth [12]. Studies have shown that people are more likely to turn to poaching when they are poverty-stricken, often as a result of marginalisation, so a vicious cycle plays out when the historical context of socio-ecological dilemmas is ignored [12,81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seemingly neutral automated environmental governance and conservation by algorithm prioritizes elements that can be captured and tracked quantitatively, elides democratic engagement in the reconciliation of value conflicts, introduces privacy concerns, and privileges those with access to technology and the resulting information, affecting who governs and how (Dallyn 2017, Bakker and Ritts 2018, Adams 2019b, Hagerman et al 2021. It renders invisible and precarious the human labor that accompanies, often in a reworked manner, techno-conservation (Lohmann 2020, Neimark et al 2020, Thakholi 2021. More insidiously, new surveillance technologies can enlist citizen scientists in state security projects (Bakker and Ritts 2018), underwrite increased violence in conservation (Duffy 2014, Kelly and Ybarra 2016, Lunstrum 2014, and lead to surveillance philanthropy (Howson 2021a).…”
Section: Technological Innovationmentioning
confidence: 99%